2017
DOI: 10.1177/0194599816685559
|View full text |Cite|
|
Sign up to set email alerts
|

Panel 3: Genetics and Precision Medicine of Otitis Media

Abstract: Objective. The objective is to perform a comprehensive review of the literature up to 2015 on the genetics and precision medicine relevant to otitis media. Data Sources. PubMed database of the National Library of Medicine. Review Methods. Two subpanels were formed comprising experts in the genetics and precision medicine of otitis media. Each of the panels reviewed the literature in their respective fields and wrote draft reviews. The reviews were shared with all panel members, and a merged draft was creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…This suggests that host genetics may play a role in engendering intra‐species diversification and genotypic variation regarding immunologic response. Identification of genetic loci that are associated with OM is an avenue of precision medicine which is currently under study and has shed light into potential disease mechanisms and novel therapeutic strategies for certain at‐risk groups (Bhutta et al, 2017; Geng et al, 2019; Lin et al, 2017).…”
Section: Clinical Relevance Of Nasopharyngeal Morphology In Humansmentioning
confidence: 99%
“…This suggests that host genetics may play a role in engendering intra‐species diversification and genotypic variation regarding immunologic response. Identification of genetic loci that are associated with OM is an avenue of precision medicine which is currently under study and has shed light into potential disease mechanisms and novel therapeutic strategies for certain at‐risk groups (Bhutta et al, 2017; Geng et al, 2019; Lin et al, 2017).…”
Section: Clinical Relevance Of Nasopharyngeal Morphology In Humansmentioning
confidence: 99%
“…Thus, differences in host PRR expression and subsequent signalling pathway activation can lead to differences in how the innate immune response is regulated and how OM disease progresses. There is growing evidence that host genetic polymorphisms in PRR genes and differences in PRR expression can dysregulate innate immune signalling pathways in response to otopathogens and therefore play a significant role in the induction and pathogenesis of OM (Lin et al, 2017). Furthermore, NTHi is recently reported to utilise phase variable epigenetic regulation to modify and adapt its phenotype but also modify host immune responses (Robledo-Avila et al, 2020), creating a shifting immunological target for the host (Parrish et al, 2019).…”
Section: Pathogen Recognition and Activation Of Signalling Pathways Within The Innate Immune Responsementioning
confidence: 99%
“…Allelic association studies have identified polymorphisms related to the development of OM in genes encoding TLR4 receptors, IL-6, IL-10 and TNF-a (Emonts et al, 2007), mannose-binding lectins (Wiertsema et al, 2006), surfactant (Ramet et al, 2001), and Mucin gene MUC5AC (Ubell et al, 2010) [for review see (Mittal et al, 2014a;Lin et al, 2017;Geng et al, 2019)]. TLR4 locus polymorphisms have also been examined in patients with RAOM or COME and demonstrated a role for TLR4 in the regulation of the innate immune response.…”
Section: Host Factors That Modulate the Mucosal Response In Ommentioning
confidence: 99%
“…Many OM mouse models are characterized by gene mutations that cause defects in craniofacial anatomy or ME cellular function, including mucin production, ciliated cell function, ET structure and function, ME cavitation, and mucosal hyperplasia. Many of these mouse mutants spontaneously develop COME and thus can serve as good models for studying COME (Bhutta et al, 2017b;Lin et al, 2017).…”
Section: Genes Involved In Anti-inflammatory Responses In Ommentioning
confidence: 99%
“…Genetics has also been shown to play a critical role in host susceptibility to OM; therefore, identifying genetic loci that are associated with OM could help to elucidate potential disease mechanisms and develop effective therapies. Many host genes identified and associated with OM have been reviewed before (Rye et al, 2011a;Kurabi et al, 2016;Bhutta et al, 2017b;Lin et al, 2017). In this review, we provide an update on the identification of new host genes, make progress in our understanding of previously identified genes in OM predisposition, and discuss the prospects for future research in this field.…”
Section: Introductionmentioning
confidence: 99%